Photo report of Mongolian pastoralists in the time of the Covid-19, February 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2021)
Photographic report
Keywords: Arid regions; Travel; Internal migration; Households; Disasters; Lockdown; Otor (Mongolia); Dzud (Mongolia); Mongolia; Mobility; COVID-19 Pandemic